Modelagem computacional da interação ponta-MoS2 em um sistema TERS usando FDTD - Sales, Victor Hugo Freitas (2021)
With the advancement of the research in nanotechnology and the increase of specificity of nanodevices, a large set of two-dimensional materials began to gain notoriety. Molybdenium disulfide (MoS2) was one of those that stood out because, as a monolayer, it’s a direct band gap semiconductor. In order to characterize such nanomaterials, one implemented technique is Tip-Enhanced Raman Spectroscopy (TERS). This technique, since its conception, has been improved due, in part, computational models that simulate the experimental environment and thus can verify how different parameters influence the final result. In this work, the Finite-Difference Time-Domain (FDTD) method will be employed through the software Meep to create a computational environment that simulates the tip and excitation of TERS experimental arrangement, in order to analyze the interaction between gold and silver tips, and MoS2 monolayer samples.